New Supervisory Control and Data Acquisition (SCADA) Based Fault Isolation System for Low Voltage Distribution Systems - Ahmed, Musse Mohamud (IEEE, 2010)
This paper proposes a new supervisory control and data acquisition (SCADA) based fault isolation system on the low voltage (415/240 V) distribution system. It presents a customized distribution automation system (DAS) for automatic operation and secure fault isolation tested in the Malaysian utility distribution system; Tenaga Nasional Berhad (TNB) distribution system. It presents the first research work on customer side automation for operating and controlling between the consumer and the substation in an automated manner. The paper focuses on the development of very secure automated fault isolation work tested to TNB distribution operating principles as the fault is detected, identified, isolated and cleared in few seconds by just clicking the mouse of laptop or desktop connected to the system. Supervisory Control and Data Acquisition (SCADA) technique has been developed and utilized to build Human Machine Interface (HMI) that provides a Graphical User Interface (GUI) functions for the engineers and technicians to monitor and control the system. Microprocessor based Remote Monitoring Devices have been used for customized software integrated to the hardware. Power Line Carrier (PLC) has been used as communication media between the consumer and the substation. As a result, complete DAS and fault isolation system has been developed for remote automated operation, cost reduction, maintenance time saving and less human intervention during faults conditions.